Characterization of carbon nanotube (MWCNT) containing P(3HB)/bioactive glass composites for tissue engineering applications - Misra, Superb K.; Ohashi, F.; Valappil, Sabeel P.; Knowles, Jonathan C.; Roy, I.; Silva, S. Ravi P.; Salih, Vehid; Boccaccini, Aldo R. (Acta Biomaterialia, 2010)
Poly(3-hydroxybutyrate) (P(3HB)) composites with bioactive glass particles and multiwall carbon nanotubes (MWCNTs) were prepared and used to identify whether the electrical properties of MWCNTs can be used to detect the bioactivity of P(3HB)/bioactive glass composites. The presence of MWCNTs (2-7 wt.%) increased the surface roughness of the composites. The presence of MWCNTs in low quantity enhanced MG-63 osteoblast-like cell attachment and proliferation compared to composites with higher concentration of MWCNTs. Current-voltage measurements demonstrated that the electrical resistance of the composites containing bioactive glass particles decreased over a 45-day immersion period in SBF, whereas composites without bioactive glass showed no significant change over the same period. © 2009 Acta Materialia Inc.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.charac
Keywords: Bioglass; Composites; Cytocompatibility; MWCNTs; Poly(3-hydroxybutyrate)